Alaska pollock gelatin sealant shows long-term efficacy and safety in a pulmonary air leakage rat model. (20th October 2022) - Yanagihara, Takahiro; Maki, Naoki; Kawamura, Tomoyuki; Kobayashi, Naohiro; Kikuchi, Shinji; Goto, Yukinobu; Ichimura, Hideo; Watanabe, Shiharu; Taguchi, Tetsushi; Sato, Yukio
Abstract: OBJECTIVES: Postoperative prolonged air leakage is a frequent complication following lung resection. We have shown the high adhesive quality of a newly developed sealant based on a hydrophobically modified Alaska pollock-derived gelatin (ApGltn) sealant in acute in vivo settings. The purpose of this study was to investigate the long-term efficacy and safety of ApGltn sealant using rats as a preclinical model. METHODS: An air leakage rat model with a 5-mm pleural defect was created, to which ApGltn sealant or fibrin sealant was applied. In both groups, the rats were evaluated on days 1, 7, 14 and 28. In the ApGltn sealant group, days 56 and 84 were added to evaluate absorption as sealant was still present on day 28. The number of rats in each subgroup was 4 (for a total of 40). Lung specimens and blood samples were obtained for histological and haematological assessment. RESULTS: No findings suggesting infection or air leakage were observed. ApGltn sealant was absorbed from day 56 to day 84. Histologically, although neutrophil and lymphocyte infiltrations on the lung side did not differ between groups, those on the sealant side were significantly less in the ApGltn sealant group. Blood sample tests revealed no significant findings suggesting inflammation or organ damage in either group. CONCLUSIONS: ApGltn sealant showed long-term sealing efficacy and safety with mild inflammation in a pulmonary air leakage rat model. ApGltn sealant is expected to be a safe and effective sealant for clinical applications. Abstract : Postoperative prolonged air leakage occurs in 5.6–17.6% of cases after lung resection surgery [1–4].